2014
DOI: 10.1126/science.1260139
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale nanoshaping of ultrasmooth 3D crystalline metallic structures

Abstract: We report a low-cost, high-throughput benchtop method that enables thin layers of metal to be shaped with nanoscale precision by generating ultrahigh-strain-rate deformations. Laser shock imprinting can create three-dimensional crystalline metallic structures as small as 10 nanometers with ultrasmooth surfaces at ambient conditions. This technique enables the successful fabrications of large-area, uniform nanopatterns with aspect ratios as high as 5 for plasmonic and sensing applications, as well as mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
134
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 177 publications
(135 citation statements)
references
References 52 publications
1
134
0
Order By: Relevance
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For friction welding, the low efficiency and welding defects are concerning. Alternatively, highpower-density laser has attracted enormous research interest and found its wide application in a broad branch of manufacturing areas including selective laser sintering and three-dimensional printing [1][2][3][4][5][6], surface nanostructuring [7][8][9][10][11][12], multimaterial joining and integration [13][14][15][16][17], material removal [18,19], and mechanical/optical property enhancements [20][21][22][23]. Characteristics, such as contact-free processing, good flexibility and tunablity, high efficiency, and throughput, make laser a feasible route for welding of 42CrMo [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…These methods allow the fabrication of homogeneously metallic nanopatterns but are costly, owing to time-consuming, multistep processes, and are also limited in preparing nanostructures with low-aspect ratios27. At present, rapid fabrication of metallic nanostructures in terms of controllability (for example, resolution, precision and uniformity), material diversity, cost and especially high-aspect ratio remains a significant challenge2829.…”
mentioning
confidence: 99%
“…Recently, Schroers and co-workers333435 succeed in nanomoulding bulk metallic glasses (BMGs) above their glass transition temperatures ( T g ) and below crystallization temperatures ( T x ), which has triggered broad research in exploring BMGs' applications such as electrochemical catalysts36 and micro/nano-electro-mechanical systems3738. However, a similar process has been considered infeasible for nanoimprinting crystalline metals below their melting temperatures ( T m )283337 because of the limitations on formability originating from size effect in plasticity439 and grain size effect3740. There has been a few attempts using templates to nanoimprint metals close to forging41, but the temperature is too low and the embossed smallest feature size is usually on the order of grain sizes.…”
mentioning
confidence: 99%
“…Existing methods to fabricate nanostructured metallic surfaces possess considerable limitations. For example, laser treatment 12,13 , shock forming 14 , and thermoplastic forming against anodized aluminum oxide (AAO) 6 exhibit difficulties with producing complex, non-planar geometries. There are also limitations on the final surface composition and crystal structure, such as those present with electrochemical dealloying [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%